1993
DOI: 10.1037/0033-2909.114.3.395
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of biculturalism: Evidence and theory.

Abstract: A vital step in the development of an equal partnership for minorities in the academic, social, and economic life of the United States involves moving away from assumptions of the linear model of cultural acquisition. In this article we review the literature on the psychological impact of being bicultural. Assimilation, acculturation, alternation, multicultural, and fusion models that have been used to describe the psychological processes, social experiences, and individual challenges and obstacles of being bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

56
1,631
10
13

Year Published

1998
1998
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,772 publications
(1,738 citation statements)
references
References 108 publications
56
1,631
10
13
Order By: Relevance
“…One potential limitation of the bilingual designs used in both Studies 2 and 3 is that results from these samples may not be generalizable to monolingual Hispanic samples (i.e., immigrants who do not speak any English). Bilingual (and bicultural) individuals may differ from monolingual individuals in particular cognitive and interpersonal characteristics (Laframboise, Coleman, & Gerton, 1993;Lambert, 1977;Reynolds, 1991). Thus, the mean levels on the Spanish and English BFI and NEO-FFI scales obtained in Studies 2 and 3 may not apply to monolingual Hispanic samples.…”
Section: Resultsmentioning
confidence: 99%
“…One potential limitation of the bilingual designs used in both Studies 2 and 3 is that results from these samples may not be generalizable to monolingual Hispanic samples (i.e., immigrants who do not speak any English). Bilingual (and bicultural) individuals may differ from monolingual individuals in particular cognitive and interpersonal characteristics (Laframboise, Coleman, & Gerton, 1993;Lambert, 1977;Reynolds, 1991). Thus, the mean levels on the Spanish and English BFI and NEO-FFI scales obtained in Studies 2 and 3 may not apply to monolingual Hispanic samples.…”
Section: Resultsmentioning
confidence: 99%
“…Different combinations of acculturation and enculturation (e.g., biculturalism, high acculturation-low enculturation, low acculturation-high enculturation, low acculturation-low enculturation) may lead to different adaptation experiences, and consequently different prevalence of psychiatric disorders. For example, bicultural individuals (those who have both acculturated to the dominant culture and retained ethnic identity through enculturation) may be able to contend with the demands of both cultures, leading to better mental health (LaFromboise, Coleman, & Gerton, 1993). Both the acquisition of U.S. cultural norms and values related to acculturation (Lara et al, 2005) and the maintenance of native cultural values, or enculturation, have been hypothesized to be linked to the mental health outcomes of different ethnic groups such as Native Americans, Asians and Latinos (Kim & Ominzo, 2006).…”
Section: Acculturation Enculturation and The Bicultural Model Of Adamentioning
confidence: 99%
“…However, recent reviews have suggested that assimilation is inadequate as a model of the experiences of ethnic minorities in that majority, individualistic culture is likely to contain elements that are viewed as inappropriate in terms of the minority group's own more collectivist cultural frames. Therefore, minority groups may seek to maintain a variety of stances other than an assimilationist one with regard to majority culture (e.g., LaFromboise, Coleman, & Gerton, 1993;Phinney, 1996). This may be particularly true in the ways in which social relations and social obligation are conceptualized (e.g., Patel et al, 1996;Triandis, Kashima, Shimada, & Villareal, 1986).…”
Section: Interplay Between Individualism and Collectivismmentioning
confidence: 99%